Method for Detection and Enumeration of Cryptosporidium parvum Oocysts in Feces, Manures, and Soils - Kuczynska, Ewa (American Society for Microbiology, 1999)
Eight concentration and purification methods were evaluated to determine percentages of recovery of Cryptosporidium parvum oocysts from calf feces. The NaCl flotation method generally resulted in the highest percentages of recovery. Based on the percentages of recovery, the amounts of fecal debris in the final oocyst preparations, the relatively short processing time (<3 h), and the low expense, the NaCl flotation method was chosen for further evaluation. Extraction efficiency was evaluated by using oocyst concentrations of 25, 50, 10(2), 10(3), 10(4), and 10(5) oocysts g of bovine feces(−1). The percentages of recovery ranged from 10.8% (25 oocysts g(−1)) to 17.0% (10(4) oocysts g(−1)) (r(2) = 0.996). A conservative estimate of the detection limit for bovine feces is ca. 30 oocysts g of feces(−1). Percentages of recovery were determined for six different types of animal feces (cow, horse, pig, sheep, deer, and chicken feces) at a single oocyst concentration (10(4) oocysts g(−1)). The percentages of recovery were highest for bovine feces (17.0%) and lowest for chicken feces (3.2%). Percentages of recovery were determined for bovine manure after 3 to 7 days of storage. The percentages of recovery ranged from 1.9 to 3.5% depending on the oocyst concentration, the time of storage, and the dispersing solution. The percentages of oocyst recovery from soils were evaluated by using different flotation solutions (NaCl, cold sucrose, ZnSO(4)), different dispersing solutions (Triton X-100, Tween 80, Tris plus Tween 80), different dispersion techniques (magnetic stirring, sonication, blending), and different dispersion times (5, 15, and 30 min). Twenty-five-gram soil samples were used to reduce the spatial variability. The highest percentages of recovery were obtained when we used 50 mM Tris–0.5% Tween 80 as the dispersing solution, dispersion for 15 min by stirring, and saturated NaCl as the flotation solution. The percentages of oocyst recovery from freshly spiked sandy loam, silty clay loam, and clay loam soils were ca. 12 to 18, 8, and 6%, respectively. The theoretical detection limits were ca. 1 to 2 oocysts g of soil(−1) depending on the soil type. The percentages of recovery without dispersant (distilled H(2)O or phosphate-buffered saline) were less than 0.1%, which indicated that oocysts adhere to soil particles. The percentages of recovery decreased with storage time, although the addition of dispersant (Tris-Tween 80) before storage appeared to partially prevent adhesion. These data indicate that the NaCl flotation method is suitable for routine detection and enumeration of oocysts from feces, manures, soils, or soil-manure mixtures.